New horizons: the management of hypertension in people with dementia - Harrison, Jennifer K.; Van Der Wardt, Veronika; Conroy, Simon P.; Stott, David J.; Dening, Tom; Gordon, Adam L.; Logan, Pip; Welsh, Tomas J.; Taggar, Jaspal; Harwood, Rowan; Gladman, John R.F. (Oxford University Press, 2016)
The optimal management of hypertension in people with dementia is uncertain. This review explores if people with dementia experience greater adverse effects from antihypertensive medications, if cognitive function is protected or worsened by controlling blood pressure (BP) and if there are subgroups of people with dementia for whom antihypertensive therapy is more likely to be harmful. Robust evidence is scant, trials of antihypertensive medications have generally excluded those with dementia. Observational data show changes in risk association over the life course, with high BP being a risk factor for cognitive decline in mid-life, while low BP is predictive in later life. It is therefore possible that excessive BP lowering in older people with dementia might harm cognition. From the existing literature, there is no direct evidence of benefit or harm from treating hypertension in people with dementia. So what practical steps can the clinician take? Assess capacity, establish patient preferences when making treatment decisions, use ambulatory monitoring to thoroughly assess BP, individualise and consider deprescribing where side effects (e.g. hypotension) outweigh the benefits. Future research might include pragmatic randomised trials of targeted deprescribing, which include patient-centred outcome measures to help support decision-making and studies to address mechanistic uncertainties.